Clinical practice professors' professional motivation and job performance by professional school nursing - Zuta Arriola, Noemi (2018)
The present research “Clinical practice professors' professional motivation and job performance by professional school nursing” by State University of Callao, has like objective determine the incidence that has the motivation in the performance, for which has been used a design of study of descriptive, correlational, comparative and cross-sectional type. For the construction of the descriptive part, an exploration of the main findings reported in the questionnaires was carried out. In addition, a study research of the forms of motivation within the professional school nursing was carried out. The study was carried out to 28 professors to verify the degree of incidence that it has in the motivation and achieve its performance within the professional school. The field research was developed with the calculation of the frequencies and the percentages of the statistical software SPSS Statistics 20 with its statistical interpretation, which serves to perform the testing of the hypotheses. Arriving at the conclusion that the motivation has a great influence on the job performance of the Clinical Practice Professors of the Professional School Nursing.